An inventory of useful threatened plant species in Vhembe Biosphere Reserve, Limpopo Province, South Africa - Luambo Jeffrey Ramarumo; ALFRED MAROYI (Society for Indonesian Biodiversity, 2020)
Abstract. Ramarumo LJ, Maroyi A. 2020. An inventory of useful threatened plant species in Vhembe Biosphere Reserve, Limpopo Province, South Africa. Biodiversitas 21: 2146-2158. Scientists and conservation managers are seeking to understand and monitor plant species that are likely to be on the verge of extinction risk. Monitoring of threatened plants’ extinction risk can be better achieved through insights about indigenous knowledge dynamics associated with those species. This study aimed to document detailed information about useful threatened plant species in the Vhembe Biosphere Reserve, Limpopo Province, South Africa. Data was collected through interviews with 203 participants and literally counting of individuals as per the IUCN’s Red List Criteria. A total of 13 useful and native threatened plants belonging to 12 families were recorded. The majority of the threatened plant species were being used for medicinal purposes only (46.0%) followed by the mixture of medicinal and ornamentals (23.0%). The frequently cited useful threatened species with UV > 0.024, RFC > 0.059 and FL > 5.911%, includes Asparagus sekukuniensis, Bowiea volubilis, Brackenridgea zanguebarica, Ocotea bullata, Rhynchosia vendae, Siphonochilus aethiopicus and Warburgia salutaris. About 47.0% of the recorded useful threatened plants were distributed in remote areas of the Thathe Von?o and its surroundings. Threatened plants with the population size < 100 adult individuals constitute an overall of 61.54% of all the recorded species. The current study provides substantial information about useful threatened plant species in the studied region. Detailed information about threatened plant species remains fundamental for making informed decisions that are important for managing species of conservation concern.